Positive electrode composition, positive electrode, and battery
A tailored positive electrode composition with specific carbon black and carbon nanotubes improves conductivity and dispersibility, addressing the limitations of existing combinations to achieve low internal resistance and enhanced discharge rate and cycle characteristics in lithium ion secondary batteries.
Patent Information
- Application Number
- JP2023530352
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-06-25
- Filing Date
- 2022-06-14
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2042-06-14
AI Technical Summary
Existing lithium ion secondary batteries do not achieve sufficiently excellent battery characteristics when using combinations of carbon nanotubes and carbon black, particularly in terms of internal resistance and discharge rate characteristics.
A positive electrode composition is formulated with specific ratios and properties of carbon black and carbon nanotubes, including BET specific surface area, average diameter, and crystallite size, to enhance conductivity and dispersibility, thereby forming efficient conductive paths within the electrode.
The composition results in lithium ion secondary batteries with low internal resistance and excellent discharge rate characteristics and cycle characteristics.
Smart Images

Figure 0007603159000005 
Figure 0007603159000001 
Figure 0007603159000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode composition, a positive electrode, and a battery. [Background technology]
[0002] In light of growing environmental and energy issues, there has been active development of technologies aimed at realizing a low-carbon society that reduces dependency on fossil fuels. Such technological development is wide-ranging, and includes the development of low-emission vehicles such as hybrid electric vehicles and electric vehicles, natural energy power generation and storage systems such as solar and wind power generation, and next-generation power transmission networks that supply electricity efficiently and reduce transmission losses.
[0003] Batteries are one of the key devices commonly required for these technologies, and high energy density is required for such batteries to miniaturize the systems. In addition, high output characteristics are required to enable stable power supply regardless of the temperature of the operating environment. Furthermore, good cycle characteristics that can withstand long-term use are also required. For this reason, conventional lead-acid batteries, nickel-cadmium batteries, and nickel-metal hydride batteries are being rapidly replaced by lithium-ion secondary batteries, which have higher energy density, output characteristics, and cycle characteristics.
[0004] Conventionally, the positive electrode of a lithium-ion secondary battery is manufactured by coating a positive electrode paste containing a positive electrode active material, a conductive material, and a binding material (also called a binder) on a current collector. Lithium-containing composite oxides such as lithium cobalt oxide and lithium manganese oxide have been used as the positive electrode active material. Since the positive electrode active material has poor conductivity, a conductive material such as carbon black has been added to the positive electrode paste in order to impart conductivity (Patent Document 1).
[0005] In recent years, there has been a demand for further improvement in the energy density of lithium ion secondary batteries. In order to improve the energy density, it has been considered to reduce the content of conductive material, which is a component in the positive electrode that does not contribute to the charge / discharge capacity, and to increase the content of the positive electrode active material. As a means for maintaining conductivity while reducing the content of conductive material, it has been proposed to use a particulate conductive material such as carbon black in combination with a fibrous conductive material having an aspect ratio higher than that of the particulate conductive material.
[0006] For example, Patent Document 2 discloses the use of a conductive additive including a three-dimensional network structure of at least two carbonaceous materials selected from the group consisting of carbon nanotubes CNT (A) having a first diameter, carbon nanotubes CNT (B) having a second diameter, graphene, and carbon black. Patent Document 3 discloses the use of carbon black having an average particle diameter of 1 nm to 100 nm, a dibutyl phthalate oil absorption of 50 ml / 100 g or more, and an iodine adsorption of 2000 mg / g or less, and a carbon nanotube having an average fiber diameter of 0.01 μm to 10 μm, an average fiber length of 1 μm to 200 μm, and a true density of 1.8 g / cm. 3 It is disclosed that the use of a mixture containing a graphitized carbon fiber having an X-ray diffraction parameter d(002) of 0.345 nm or less stabilizes the conductive path in the positive electrode, thereby reducing the initial internal resistance and providing a nonaqueous electrolyte battery with excellent rapid large current charging and discharging and long-term reliability. Patent Document 4 also discloses that a lithium ion battery electrode containing (a) fine fibrous carbon having a diameter of less than 100 nm, (b) fibrous carbon having a diameter of 100 nm or more, and / or (c) nonfibrous conductive carbon as a conductive material provides a lithium ion battery electrode with low electrode surface resistance, excellent discharge capacity, and excellent cycle characteristics. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2008-227481 A [Patent Document 2] JP 2016-25077 A [Patent Document 3] JP 2001-126733 A [Patent Document 4] JP 2010-238575 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, the combinations of carbon nanotubes and carbon black described in Patent Documents 2 to 4 did not provide sufficiently excellent battery characteristics.
[0009] In view of the above problems and circumstances, the present invention aims to provide a positive electrode composition capable of obtaining a lithium ion secondary battery having a small internal resistance and excellent discharge rate characteristics and cycle characteristics. Another object of the present invention is to provide a positive electrode containing the positive electrode composition. Another object of the present invention is to provide a battery including the positive electrode. [Means for solving the problem]
[0010] The present invention relates to, for example, the following <1> ~ <8> Regarding. <1> The carrier contains carbon black, carbon nanotubes, an active material, and a binder, and the carbon black has a particle size of 100 to 400 m. 2 / g BET specific surface area and a crystallite size (Lc) of 15 to 26 Å, the carbon nanotubes have an average diameter of 5 to 15 nm, and the ratio of the average diameter to the BET specific surface area of the carbon nanotubes (average diameter / BET specific surface area) is 0.01 to 0.068 nm / (m 2 / g). In the present specification, when a tilde symbol (~) is used to express, for example, "x~y" (x and y are numerical values), it means "x or more and y or less." Specifically, "100 to 400 m 2 / g BET specific surface area is 2 / g or more 400m 2 / g or less." <2> The carbon black has an average primary particle size of 17 to 30 nm. <1> The positive electrode composition according to claim 1 . <3> a ratio (S2 / S1) of a peak area (S2) of a peak having a mass number of m / z of 128 to a peak area (S1) of a peak having a mass number of m / z of 57 detected by thermal desorption spectrometry of the carbon black is 0.2 to 1.9; <1> or <2> The positive electrode composition according to claim 1 . <4> The crystallite size (Lc) of the carbon black is 15 to 20 Å. <1> ~ <3> 2. The positive electrode composition according to claim 1 . <5> The BET specific surface area of the carbon black is 170 to 400 m 2 / g, <1> ~ <4> 2. The positive electrode composition according to claim 1 . <6> The average diameter of the carbon nanotubes is 5 to 10 nm. <1> ~ <5> 2. The positive electrode composition according to claim 1 . <7> The content of the carbon black is 40 to 90 mass% based on the total content of the carbon black and the carbon nanotubes. <1> ~ <6> 2. The positive electrode composition according to claim 1 . <8> <1> ~ <7> A positive electrode comprising the positive electrode composition according to any one of claims 1 to 5. <9> <8> A battery comprising the positive electrode according to claim 1. Effect of the Invention
[0011] According to the present invention, it is possible to provide a positive electrode composition capable of obtaining a lithium ion secondary battery having a small internal resistance and excellent discharge rate characteristics and cycle characteristics. Also, according to the present invention, it is possible to provide a positive electrode including the positive electrode composition. Also, according to the present invention, it is possible to provide a battery including the positive electrode. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a diagram showing an example of carbon black used in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present invention will be described in detail. The positive electrode composition according to this embodiment contains carbon black, carbon nanotubes, an active material, and a binder. In the positive electrode composition according to this embodiment, the carbon black has a particle size of 100 to 400 μm. 2 The carbon nanotubes have a BET specific surface area of 0.01 to 0.068 nm / (m / g) and a crystallite size (Lc) of 15 to 26 Å, and the carbon nanotubes have an average diameter of 5 to 15 nm. The ratio of the average diameter to the BET specific surface area of the carbon nanotubes (average diameter / BET specific surface area) is 0.01 to 0.068 nm / (m 2 / g).
[0014] The positive electrode composition according to this embodiment contains, as a conductive material, carbon black having a specific BET specific surface area and a specific crystallite size (Lc), and carbon nanotubes having a specific average diameter and a specific ratio (average diameter / BET specific surface area).
[0015] The basic role of the conductive material is to impart conductivity to the poorly conductive positive electrode active material. In addition, in lithium ion secondary batteries, the positive electrode active material expands and contracts as the charge and discharge are repeated, gradually losing contact between the positive electrode active materials, but the conductive material also plays a role in connecting the positive electrode active materials that have lost contact and preventing the conductivity from being impaired. If the dispersibility of the conductive material in the positive electrode active material is poor, the positive electrode active material and the conductive material cannot be in sufficient contact with each other, making it difficult to form a conductive path, and the performance of the active material cannot be fully brought out. As a result, since parts with poor conductivity appear locally in the positive electrode, the active material is not fully utilized, the discharge capacity is reduced, and the battery life is shortened. In addition, it is possible to increase the content of the conductive material in order to secure the conductive path, but from the viewpoint of improving the battery characteristics, it is desirable to reduce the content of the conductive material that does not contribute to the charge and discharge capacity in the positive electrode and increase the content of the positive electrode active material.
[0016] In this embodiment, the combination of the specific carbon black and the specific carbon nanotubes makes it easy for the conductive material to be uniformly dispersed in the positive electrode composition. In addition, the combination allows the conductive material to efficiently form a conductive path in the positive electrode composition, so that in this embodiment, excellent battery characteristics can be maintained even if the content of the conductive material is reduced.
[0017] The carbon black may be any carbon black commonly used as a conductive material for batteries, such as acetylene black, furnace black, channel black, etc. The carbon black is preferably acetylene black, from the viewpoint of excellent purity and ease of obtaining excellent battery characteristics.
[0018] The BET specific surface area of carbon black is 100 to 400 m 2 / g. The BET specific surface area of the carbon blank is 100 m 2 / g or more, the number of electrical contacts with the active material and the conductive material increases, and the effect of imparting conductivity is good, resulting in excellent battery characteristics. 2 / g or less, the interactions between the solvent and the conductive material, and between the conductive materials themselves, are small, making it easier for the conductive material to disperse uniformly in the active material, which makes it easier to form conductive paths and results in excellent battery characteristics. The BET specific surface area of carbon black can be measured by the static capacitance method in accordance with JIS Z8830, using nitrogen as the adsorbate.
[0019] The BET specific surface area of the carbon black is preferably 130 m from the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics. 2 / g or more, more preferably 150m 2 / g or more, 170m 2 / g or more, 200m 2 / g or more, 220m 2 / g or more or 240m 2 From the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics, the BET specific surface area of the carbon black is preferably 400 m2 / g or less, preferably 370m 2 / g or less, 350m 2 / g or less, 330m 2 / g or less, 300m 2 / g or more, 280m 2 / g or more, or 260m 2 From these viewpoints, the BET specific surface area of the carbon black may be, for example, 100 to 400 m 2 / g, 100-370m 2 / g, 100-350m 2 / g, 100-330m 2 / g, 100-300m 2 / g, 100-280m 2 / g, 100-260m 2 / g, 130-400m 2 / g, 130-370m 2 / g, 130-350m 2 / g, 130-330m 2 / g, 130-300m 2 / g, 130-280m 2 / g, 130-260m 2 / g, 150-400m 2 / g, 150-370m 2 / g, 150-350m 2 / g, 150-330m 2 / g, 150-300m 2 / g, 150-280m 2 / g, 150-260m 2 / g, 170-400m 2 / g, 170-370m 2 / g, 170-350m 2 / g, 170-330m 2 / g, 170-300m 2 / g, 170-280m 2 / g, 170-260m 2 / g, 200-400m 2 / g, 200-370m 2 / g, 200-350m 2 / g, 200-330m 2 / g, 200-300m 2 / g, 200-280m2 / g, 200-260m 2 / g, 220-400m 2 / g, 220-370m 2 / g, 220-350m 2 / g, 220-330m 2 / g, 220-300m 2 / g, 220-280m 2 / g, 220-260m 2 / g, 240-400m 2 / g, 240-370m 2 / g, 240-350m 2 / g, 240-330m 2 / g, 240-300m 2 / g, 240-280m 2 / g, or 240-260m 2 / g.
[0020] The crystallite size (Lc) of carbon black is 15 to 26 Å. When the crystallite size (Lc) is 15 Å or more, π electrons can easily move in the crystal layer, and a conductive path that carries electrons from the current collector to the active material can easily be formed, resulting in excellent battery characteristics. In addition, when the crystallite size (Lc) is 15 Å or more, the carbon black is less likely to be oxidized and decomposed even when used under high voltage. When the crystallite size (Lc) is 26 Å or less, the particle shape of the carbon black is more likely to be rounded, so that the interaction between particles is reduced and the carbon black is more likely to be uniformly dispersed in the active material, which makes it easier to form a conductive path, resulting in excellent battery characteristics. The crystallite size (Lc) of carbon black can be measured in accordance with JIS R7651. The crystallite size (Lc) of carbon black means the crystallite size in the c-axis direction of the carbon black crystal layer.
[0021] From the viewpoint of reducing the internal resistance and from the viewpoint of improving the discharge rate characteristics and cycle characteristics, the crystallite size (Lc) of the carbon black may be 24 Å or less or 22 Å or less, preferably 20 Å or less, and may be 18 Å or less. The crystallite size (Lc) of the carbon black may be 16 Å or more, 18 Å or more, or 20 Å or more. From these viewpoints, the crystallite size (Lc) of the carbon black may be, for example, 15 to 26 Å, 15 to 24 Å, 15 to 22 Å, 15 to 20 Å, 15 to 18 Å, 16 to 26 Å, 16 to 24 Å, 16 to 22 Å, 16 to 20 Å, 16 to 18 Å, 18 to 26 Å, 18 to 24 Å, 18 to 22 Å, 18 to 20 Å, 20 to 26 Å, 20 to 24 Å, or 20 to 22 Å.
[0022] The average primary particle diameter of carbon black may be 17 to 30 nm. When the average primary particle diameter of carbon black is 17 nm or more, the interaction between the solvent and the conductive material and between the conductive materials is reduced, and the carbon black is easily dispersed uniformly in the active material, so that the conductive path is easily formed, and excellent battery characteristics are more easily obtained. When the average primary particle diameter of carbon black is 30 nm or less, the number of electrical contacts with the active material and the conductive material is increased, and the effect of imparting conductivity is good, so that excellent battery characteristics are more easily obtained. The average primary particle diameter of carbon black means the average value of the circle equivalent diameter measured based on the image when observing carbon black with a transmission electron microscope (TEM). Specifically, the average primary particle diameter of carbon black is obtained by taking 10 images of carbon black at a magnification of 100,000 times using a transmission electron microscope JEM-2000FX (manufactured by JEOL Ltd.), measuring the circle equivalent diameters of 200 primary particles of carbon black randomly extracted from the obtained images by image analysis, and calculating the arithmetic average.
[0023] From the viewpoint of reducing the internal resistance and from the viewpoint of improving the discharge rate characteristics and cycle characteristics, the average primary particle diameter of the carbon black may be 26 nm or less, 24 nm or less, 22 nm or less, or 20 nm or less. The average primary particle diameter of the carbon black may be 18 nm or more, or 20 nm or more. From these viewpoints, the average primary particle diameter of the carbon black may be, for example, 17 to 30 nm, 17 to 26 nm, 17 to 24 nm, 17 to 22 nm, 17 to 20 nm, 18 to 30 nm, 18 to 26 nm, 18 to 24 nm, 18 to 22 nm, or 18 to 20 nm.
[0024] When the peak area of the peak of mass number m / z 57 detected by thermal desorption spectrometry of carbon black is S1 and the peak area of the peak of mass number m / z 128 is S2, the ratio (S2 / S1) of the peak area S2 to the peak area S1 is preferably 0.2 to 1.9. The ratio (S2 / S1) indicates the proportion of organic components adsorbed on the surface of the carbon black. When the ratio (S2 / S1) is 1.9 or less, the organic components adsorbed on the surface of the carbon black are sufficiently reduced, and the decrease in conductivity caused by the organic components trapping π electrons is significantly suppressed. In addition, when the ratio (S2 / S1) is 0.2 or more, the organic components adsorbed on the surface of the carbon black play the role of a dispersant, improving the dispersibility in the solvent, and thus further reducing the viscosity of the slurry. The peak area S1 of the peak of mass number m / z 57 and the peak area S2 of the peak of mass number m / z 128 can be measured by evolved gas mass spectrometry (EGA-MS). For example, carbon black is placed in a gas chromatograph mass spectrometer equipped with a pyrolysis device, and after being held at 50° C. for 5 minutes in an atmospheric pressure He flow, the temperature is raised to 800° C. at 80° C. / min, and mass analysis of the components desorbed by the temperature rise can be performed to measure the peak area S1 of the peak with mass number m / z 57 and the peak area S2 of the peak with mass number m / z 128. More specifically, the measurements can be performed by the method described in the Examples below.
[0025] From the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics, the ratio (S2 / S1) may be 1.5 or less, 1.0 or less, 0.8 or less, 0.6 or less, 0.5 or less, 0.4 or less, or 0.3 or less. The ratio (S2 / S1) may be 0.25 or more, or 0.3 or more. From these viewpoints, the ratio (S2 / S1) may be, for example, 0.2 to 1.9, 0.2 to 1.5, 0.2 to 1.0, 0.2 to 0.8, 0.2 to 0.6, 0.2 to 0.5, 0.2 to 0.4, 0.2 to 0.3, 0.25 to 1.9, 0.25 to 1.5, 0.25 to 1.0, 0.25 to 0.8, 0.25 to 0.6, 0.25 to 0.5, 0.25 to 0.4, 0.25 to 0.3, 0.3 to 1.9, 0.3 to 1.5, 0.3 to 1.0, 0.3 to 0.8, 0.3 to 0.6, 0.3 to 0.5, or 0.3 to 0.4.
[0026] From the viewpoint of excellent electrical conductivity, the volume resistivity of carbon black may be 0.30 Ω·cm or less or 0.25 Ω·cm or less. The volume resistivity of carbon black is measured in a compressed state under a load of, for example, 7.5 MPa.
[0027] The ash content and moisture content of the carbon black are not particularly limited. The ash content of the carbon black may be, for example, 0.04% by mass or less, and the moisture content of the carbon black may be, for example, 0.10% by mass or less.
[0028] From the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics, the content of carbon black may be 0.01 mass% or more, 0.1 mass% or more, 0.3 mass% or more, 0.5 mass% or more, or 0.7 mass% or more based on the total mass of the solid content in the positive electrode composition. The content of carbon black may be 5 mass% or less, 3 mass% or less, 1 mass% or less, 0.9 mass% or less, or 0.7 mass% or less based on the total mass of the solid content in the positive electrode composition. From these viewpoints, the content of carbon black may be, for example, 0.01 to 5 mass%, 0.01 to 3 mass%, 0.01 to 1 mass%, 0.01 to 0.9 mass%, 0.01 to 0.7 mass%, 0.1 to 5 mass%, 0.1 to 3 mass%, 0.1 to 1 mass%, 0.1 to 0.9 mass%, 0.1 to 0.7 mass%, 0.3 to 5 mass%, 0.3 to 3 mass%, 0.3 to 1 mass%, 0.3 to 0.9 mass%, 0.3 to 0.7 mass%, 0.5 to 5 mass%, 0.5 to 3 mass%, 0.5 to 1 mass%, 0.5 to 0.9 mass%, 0.5 to 0.7 mass%, 0.7 to 5 mass%, 0.7 to 3 mass%, 0.7 to 1 mass%, or 0.7 to 0.9 mass%, based on the total mass of the solids in the positive electrode composition.
[0029] The carbon black content may be 10% by mass or more, 40% by mass or more, or 60% by mass or more, and may be 95% by mass or less, 90% by mass or less, or 80% by mass or less, based on the total content of the carbon black and the carbon nanotubes, from the viewpoint of reducing the internal resistance and from the viewpoint of improving the discharge rate characteristics and cycle characteristics. The carbon black content is preferably 40 to 90% by mass based on the total content of the carbon black and the carbon nanotubes, from the viewpoint of reducing the internal resistance and from the viewpoint of improving the discharge rate characteristics and cycle characteristics. When the carbon black content is 40 to 90% by mass, the carbon black easily forms a conductive path between the active materials in the positive electrode composition, and the nonaqueous electrolyte is easily held in the vicinity of the active materials. In addition, the carbon nanotubes easily form a conductive path on the surface of the active materials, and an electrode structure is formed, so that an electrode having a good conductive path and ion conductivity is easily obtained, and a battery having excellent battery characteristics is easily obtained. From these viewpoints, the carbon black content may be, for example, 10 to 95 mass%, 10 to 90 mass%, 10 to 80 mass%, 40 to 95 mass%, 40 to 90 mass%, 40 to 80 mass%, 60 to 95 mass%, 60 to 90 mass%, or 60 to 80 mass%, based on the total content of carbon black and carbon nanotubes.
[0030] The above carbon black can be produced, for example, by a production method including a synthesis step of treating a raw material gas containing hydrocarbons in a cylindrical cracking furnace to obtain carbon black, and a purification step of removing magnetic foreign matter from the carbon black obtained in the synthesis step by using a magnet.
[0031] In the synthesis step, the raw material gas is treated in a cylindrical cracking furnace. The cylindrical cracking furnace may, for example, include a pyrolysis section for carrying out a pyrolysis reaction of hydrocarbons and an aging section for modifying the pyrolysis reaction product. The cylindrical cracking furnace may further include a supply port for supplying the raw material gas to the pyrolysis section and a recovery port for recovering the carbon black produced from the aging section.
[0032] In the thermal decomposition section, the supplied raw material gas preferably resides at a temperature of 1900°C or higher for 30 to 150 seconds. By setting the residence time of the raw material gas to 30 seconds or more, the completion of the thermal decomposition reaction and the formation of carbon aerosol due to the development of a chain structure can be more reliably carried out. Furthermore, by setting the residence time of the raw material gas to 150 seconds or less, the aggregation of carbon aerosol is suppressed, making it easier to remove magnetic foreign matter in the purification step, and making it easier to obtain high-purity carbon black.
[0033] In the maturation section, the pyrolysis reaction product supplied from the pyrolysis section preferably resides at a temperature of 1700°C or higher for 20 to 90 seconds. When the residence time of the pyrolysis reaction product is 20 seconds or more, carbon aerosol is modified and aggregates are developed, making it easier to obtain higher quality carbon black. Furthermore, when the residence time of the pyrolysis reaction product is 90 seconds or less, the agglomeration of carbon aerosol is suppressed, making it easier to remove magnetic foreign matter in the purification step, and making it easier to obtain high purity carbon black.
[0034] The residence times in the pyrolysis section and the aging section can be appropriately adjusted by adjusting the linear gas velocity of the gas flowing through each section. The residence time in the aging section is preferably shorter than the residence time in the pyrolysis section. That is, the linear gas velocity in the aging section is preferably faster than the linear gas velocity in the pyrolysis section.
[0035] In this embodiment, the raw material gas preferably contains acetylene as a carbon source. The content of the carbon source (e.g., acetylene) in the raw material gas is, for example, 10% by volume or more, preferably 20% by volume or more, more preferably 30% by volume or more, and may be 100% by volume. The content of each component in the raw material gas is expressed as a volume ratio based on the volume at 100°C and 1 atm.
[0036] The raw material gas may further contain other hydrocarbons other than the carbon source (e.g., acetylene). Examples of other hydrocarbons include methane, ethane, propane, ethylene, propylene, butadiene, benzene, toluene, xylene, gasoline, kerosene, light oil, heavy oil, etc. By adding these other hydrocarbons, the reaction temperature can be changed to increase or decrease the specific surface area of the carbon black. The other hydrocarbons are preferably selected from the group consisting of aromatic hydrocarbons such as benzene and toluene, and unsaturated hydrocarbons such as ethylene and propylene.
[0037] When the raw material gas contains acetylene and other hydrocarbons, the content of the other hydrocarbons is, for example, 0.1 to 99 parts by volume, preferably 0.2 to 50 parts by volume, and more preferably 0.3 to 30 parts by volume, relative to 100 parts by volume of acetylene. That is, the content of the other hydrocarbons may be, for example, 0.1 to 99 parts by volume, 0.1 to 50 parts by volume, 0.1 to 30 parts by volume, 0.2 to 99 parts by volume, 0.2 to 50 parts by volume, 0.2 to 30 parts by volume, 0.3 to 99 parts by volume, 0.3 to 50 parts by volume, or 0.3 to 30 parts by volume, relative to 100 parts by volume of acetylene.
[0038] The raw material gas may further contain water vapor gas, oxygen gas, hydrogen gas, carbon dioxide gas, etc. As these gases, it is preferable to use high purity gases with a purity of 99.9% by volume or more. By using such high purity gases, it tends to be easier to produce carbon black with less magnetic foreign matter and stable BET specific surface area and oil absorption.
[0039] The content of the water vapor gas may be, for example, 0 to 80 parts by volume, preferably 0.1 to 70 parts by volume, more preferably 1 to 60 parts by volume, and even more preferably 3 to 55 parts by volume, relative to 100 parts by volume of the carbon source (e.g., acetylene) in the raw material gas. When the content of the water vapor gas is within the above range, the BET specific surface area of the carbon black tends to be larger. That is, the content of the water vapor gas may be, for example, 0 to 80 parts by volume, 0 to 70 parts by volume, 0 to 60 parts by volume, 0 to 55 parts by volume, 0.1 to 80 parts by volume, 0.1 to 70 parts by volume, 0.1 to 60 parts by volume, 0.1 to 55 parts by volume, 1 to 80 parts by volume, 1 to 70 parts by volume, 1 to 60 parts by volume, 1 to 55 parts by volume, 3 to 80 parts by volume, 3 to 70 parts by volume, 3 to 60 parts by volume, or 3 to 55 parts by volume, relative to 100 parts by volume of the carbon source (e.g., acetylene) in the raw material gas.
[0040] In the synthesis process, it is preferable to supply oxygen gas to the pyrolysis section together with the raw material gas, and it is more preferable to supply the oxygen gas to the pyrolysis section by spraying the oxygen gas from around the supply port through which the raw material gas is supplied to the pyrolysis section.
[0041] The cylindrical cracking furnace preferably has an oxygen gas nozzle near the raw material gas supply port, and more preferably has a plurality of nozzles provided at equal intervals so as to surround the supply port. The number of nozzles is preferably 3 or more, more preferably 3 to 8.
[0042] The cylindrical cracking furnace may also be equipped with a nozzle having a multiple tube structure (e.g., a double tube structure, a triple tube structure, etc.) having a raw material gas supply port and an injection port for injecting oxygen gas from the periphery thereof. In the case of a double tube structure, for example, the raw material gas may be injected from a gap on the inner tube side, and the oxygen gas may be injected from a gap on the outer tube side. In the case of a triple tube structure consisting of an inner tube, a middle tube, and an outer tube, for example, the oxygen gas may be injected from a gap formed by the outer wall of the middle tube and the inner wall of the outer tube, and the raw material gas may be injected from the remaining gap.
[0043] The amount of oxygen gas injected is not particularly limited unless the production yield of carbon black is taken into consideration. Carbon black can be produced even if more oxygen gas than necessary is injected. The amount of oxygen gas injected may be, for example, 0 to 300 parts by volume, 0 to 250 parts by volume, 0 to 220 parts by volume, or 0 to 200 parts by volume, preferably 0.1 to 190 parts by volume, more preferably 0.5 to 180 parts by volume, and even more preferably 1 to 160 parts by volume, relative to 100 parts by volume of the carbon source (e.g., acetylene) in the raw material gas. When the amount of oxygen gas injected is increased, the BET specific surface area of the carbon black and the above ratio (S2 / S1) tend to become larger, and when the amount of oxygen gas injected is decreased, the primary particle size of the carbon black tends to become larger. That is, the injection amount of oxygen gas is, for example, 0 to 300 parts by volume, 0 to 250 parts by volume, 0 to 220 parts by volume, 0 to 200 parts by volume, 0 to 190 parts by volume, 0 to 180 parts by volume, 0 to 160 parts by volume, 0.1 to 300 parts by volume, 0.1 to 250 parts by volume, 0.1 to 220 parts by volume, 0.1 to 200 parts by volume, 0.1 to 190 parts by volume, 0 It may be 0.1 to 180 parts by volume, 0.1 to 160 parts by volume, 0.5 to 300 parts by volume, 0.5 to 250 parts by volume, 0.5 to 220 parts by volume, 0.5 to 200 parts by volume, 0.5 to 190 parts by volume, 0.5 to 180 parts by volume, 0.5 to 160 parts by volume, 1 to 300 parts by volume, 1 to 250 parts by volume, 1 to 220 parts by volume, 1 to 200 parts by volume, 1 to 190 parts by volume, 1 to 180 parts by volume, or 1 to 160 parts by volume.
[0044] In the synthesis step, the primary particle size, BET specific surface area, and crystallite size (Lc) of the resulting carbon black can be adjusted by, for example, adjusting the addition rate of hydrocarbons other than acetylene, the amount of oxygen gas injected, etc.
[0045] The purification step is a step of removing magnetic foreign matter from the carbon black obtained in the synthesis step using a magnet. The purification step may be, for example, a step of removing magnetic foreign matter from the carbon black obtained in the synthesis step by contacting the carbon black obtained in the synthesis step with a magnet or placing the carbon black in the vicinity of a magnet (for example, passing the carbon black in the vicinity of a magnet).
[0046] The maximum surface magnetic flux density of the magnet is not particularly limited, but may be, for example, 700 mT or more, preferably 1000 mT or more, more preferably 1200 mT or more. This allows fine magnetic foreign matter attached to the carbon black to be more strongly adsorbed, making it easier to obtain carbon black with a lower nickel content. The upper limit of the maximum surface magnetic flux density of the magnet is not particularly limited, and may be, for example, 1400 mT or less. That is, the maximum surface magnetic flux density of the magnet may be, for example, 700 to 1400 mT, 1000 to 1400 mT, or 1200 to 1400 mT.
[0047] The purification step may be a step of removing magnetic foreign matter from the carbon black so that the nickel content is 50 ppb or less (preferably 40 ppb or less, more preferably 30 ppb or less, and even more preferably 20 ppb or less). There is no particular restriction on the lower limit of the nickel content, but the nickel content in the carbon black may be, for example, 1 ppb or more, and from the viewpoint of cost and productivity, it may be 10 ppb or more, or 15 ppb or more. That is, the nickel content in the carbon black may be, for example, 1 to 50 ppb, 1 to 40 ppb, 1 to 30 ppb, 1 to 20 ppb, 10 to 50 ppb, 10 to 40 ppb, 10 to 30 ppb, 10 to 20 ppb, 15 to 50 ppb, 15 to 40 ppb, 15 to 30 ppb, or 15 to 20 ppb.
[0048] The positive electrode composition according to this embodiment contains carbon nanotubes as a conductive material. The carbon nanotubes have an average diameter of 5 to 15 nm, and the ratio of the average diameter to the BET specific surface area of the carbon black (average diameter / BET specific surface area) is 0.01 to 0.068 nm / (m 2 In this embodiment, the average diameter of the carbon nanotubes is small, 5 to 15 nm, and the ratio of the average diameter to the BET specific surface area of the carbon nanotubes is 0.01 to 0.068 nm / (m 2 / g), many conductive paths can be formed in the positive electrode.
[0049] The average diameter of carbon nanotubes is 5 to 15 nm. When the average diameter of carbon black is 5 nm or more, the interaction between the solvent and the conductive material and between the conductive materials is reduced, which makes it easier to disperse uniformly in the active material, making it easier to form conductive paths, and making it easier to obtain excellent battery characteristics. When the average diameter of carbon black is 15 nm or less, there are more electrical contacts with the active material and the conductive material, which improves the effect of imparting conductivity, making it easier to obtain excellent battery characteristics.
[0050] The average diameter of the carbon nanotubes is preferably 12 nm or less, more preferably 10 nm or less, and may be 8 nm or less, or 6 nm or less, from the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics. The average diameter of the carbon nanotubes may be 6 nm or more. From these viewpoints, the average diameter of the carbon nanotubes may be, for example, 5 to 15 nm, 5 to 12 nm, 5 to 10 nm, 5 to 8 nm, 5 to 6 nm, 6 to 15 nm, 6 to 12 nm, 6 to 10 nm, or 6 to 8 nm. The average diameter of the carbon nanotubes means the average value of the diameters measured based on the images of the carbon nanotubes observed with a transmission electron microscope (TEM), and specifically, the average diameter of the carbon nanotubes is obtained by taking 10 images of the carbon nanotubes at a magnification of 200,000 times using a transmission electron microscope JEM-2000FX (manufactured by JEOL Ltd.), measuring the diameters of 100 carbon nanotubes randomly selected from the obtained images by image analysis, and calculating the arithmetic average.
[0051] The BET specific surface area of carbon nanotubes is 170 to 320 m 2 / g. The BET specific surface area of the carbon nanotubes is preferably 170 m 2 When the BET specific surface area of the carbon nanotubes is 320 m / g or more, the number of electrical contacts with the active material and the conductive material increases, and the effect of imparting conductivity is good, making it easier to obtain excellent battery characteristics. 2 / g or less, the interactions between the solvent and the conductive material, and between the conductive materials themselves, are reduced, and the conductive materials are more likely to disperse uniformly in the active material, which makes it easier to form conductive paths and therefore makes it easier to obtain excellent battery characteristics. The BET specific surface area of carbon nanotubes can be measured by the static capacitance method in accordance with JIS Z8830, using nitrogen as the adsorbate.
[0052] The BET specific surface area of the carbon nanotube is set to 180m from the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics. 2 / g or more, 200m 2 / g or more, 230m 2 / g or more, 250m 2 / g or more, 280m 2 / g or more, or 300m 2 From the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics, the BET specific surface area of the carbon nanotube is preferably 300 m 2 From these viewpoints, the BET specific surface area of the carbon nanotube may be, for example, 170 to 320 m 2 / g, 170-300m 2 / g, 180-320m 2 / g, 180-300m 2 / g, 200-320m 2 / g, 200-300m 2 / g, 230-320m 2 / g, 230-300m 2 / g, 250-320m 2 / g, 250-300m 2 / g, 280-320m 2 / g, 280-300m 2 / g, or 300-320m 2 / g.
[0053] The ratio of the average diameter of carbon nanotubes to the BET specific surface area of carbon black (average diameter / BET specific surface area) is 0.01 to 0.068 nm / (m 2 / g). The average diameter / BET specific surface area is the value obtained by dividing the average diameter of the carbon nanotubes by the BET specific surface area of the carbon nanotubes. 2 With an average diameter / BET specific surface area of 0.068 nm / (m2) or more, the carbon nanotubes are less likely to become entangled with each other and are more likely to be dispersed uniformly in the active material, which makes it easier to form conductive paths and results in excellent battery characteristics. 2 / g or less, the number of carbon nanotubes per unit weight increases, allowing electricity to flow efficiently throughout the active material, resulting in excellent battery characteristics.
[0054] The average diameter / BET specific surface area is set to 0.06 nm / (m 2 / g) or less, 0.04nm / (m 2 / g) or less, 0.03nm / (m 2 / g) or less, or 0.02 nm / (m 2 From the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics, the average diameter / BET specific surface area may be 0.02 nm / (m 2 From these viewpoints, the average diameter / BET specific surface area may be, for example, 0.01 to 0.068 nm / (m 2 / g), 0.01~0.06nm / (m 2 / g), 0.01~0.04nm / (m 2 / g), 0.01~0.03nm / (m 2 / g), 0.01~0.02nm / (m 2 / g), 0.02~0.068nm / (m 2 / g), 0.02~0.06nm / (m 2 / g), 0.02~0.04nm / (m 2 / g), or 0.02~0.03nm / (m 2 / g).
[0055] The carbon nanotube content may be 0.01% by mass or more, 0.05% by mass or more, 0.1% by mass or more, 0.2% by mass or more, or 0.3% by mass or more, based on the total mass of the solid content in the positive electrode composition, from the viewpoint of reducing the internal resistance and improving the discharge rate characteristics and cycle characteristics. The carbon nanotube content may be 3% by mass or less, 1% by mass or less, 0.9% by mass or less, 0.5% by mass or less, or 0.3% by mass or less, based on the total mass of the solid content in the positive electrode composition. From the above viewpoints, the content of the carbon nanotubes is, for example, 0.01 to 3 mass%, 0.01 to 1 mass%, 0.01 to 0.9 mass%, 0.01 to 0.5 mass%, 0.01 to 0.3 mass%, 0.05 to 3 mass%, 0.05 to 1 mass%, 0.05 to 0.9 mass%, 0.05 to 0.5 mass%, 0.05 to 0. 3% by mass, 0.1-3% by mass, 0.1-1% by mass, 0.1-0.9% by mass, 0.1-0.5% by mass, 0.1-0.3% by mass, 0.2-3% by mass, 0.2-1% by mass, 0.2 It may be ~0.9% by mass, 0.2-0.5% by mass, 0.2-0.3% by mass, 0.3-3% by mass, 0.3-1% by mass, 0.3-0.9% by mass, or 0.3-0.5% by mass.
[0056] From the viewpoint of reducing the internal resistance and from the viewpoint of improving the discharge rate characteristics and cycle characteristics, the content of the carbon nanotubes may be 5% by mass or more, 10% by mass or more, or 20% by mass or more, and may be 90% by mass or less, 60% by mass or less, or 40% by mass or less, based on the total content of the carbon black and the carbon nanotubes. From these viewpoints, the content of the carbon nanotubes may be, for example, 5 to 90% by mass, 5 to 60% by mass, 5 to 40% by mass, 10 to 90% by mass, 10 to 60% by mass, 10 to 40% by mass, 20 to 90% by mass, 20 to 60% by mass, or 20 to 40% by mass, based on the total content of the carbon black and the carbon nanotubes. In this embodiment, the ratio of the average diameter to the BET specific surface area is 0.01 to 0.068 nm / (m 2 / g), sufficient conductive paths can be formed even if the carbon nanotube content is small (for example, even if the carbon nanotube content is 60 mass % or less based on the total content of carbon black and carbon nanotubes).
[0057] The carbon nanotubes can be produced by a conventionally known method for producing carbon nanotubes. For example, a powder catalyst in which iron is supported on magnesia (magnesium oxide) is placed over the entire horizontal cross section of a vertical reactor, methane is passed through the reactor in the vertical direction, and the methane and the catalyst are brought into contact at 500 to 1200°C, and the resulting product (unoxidized carbon nanotubes) is then oxidized. The carbon nanotubes produced by the above method for producing carbon nanotubes can be produced by the following steps. The carbon nanotubes are made of several graphene layers, have an average diameter of 5 to 15 nm, and have a BET specific surface area of 160 to 300 nm. 2 / g of carbon nanotubes can be obtained.
[0058] The oxidation treatment of the product may be, for example, a calcination treatment. The temperature of the calcination treatment is not particularly limited as long as the carbon nanotubes contained in the positive electrode composition according to the present embodiment can be obtained, and may be, for example, 300 to 1000 ° C. The temperature of the calcination treatment is affected by the atmospheric gas, so that it is preferable to perform the calcination treatment at a relatively low temperature when the oxygen concentration is high, and at a relatively high temperature when the oxygen concentration is low. Specifically, the calcination treatment of the product may be performed in the atmosphere within a range of the combustion peak temperature of the carbon nanotubes before the oxidation treatment ± 50 ° C., but when the oxygen concentration is higher than the atmosphere, the calcination is performed at a temperature range lower than the calcination peak temperature, and when the oxygen concentration is lower than the atmosphere, a temperature range higher than the calcination peak temperature is selected. In particular, when performing the calcination treatment of the carbon nanotubes before the oxidation treatment in the atmosphere, it is preferable to perform the calcination treatment within a range of the combustion peak temperature of the carbon nanotubes before the oxidation treatment ± 15 ° C.
[0059] The oxidation treatment of the above product may be a treatment with hydrogen peroxide, mixed acid, nitric acid, or the like. As a method of treating the above product with hydrogen peroxide, for example, a method of mixing the above product in 34.5% hydrogen peroxide water to 0.01 to 10 mass % and reacting at a temperature of 0 to 100 ° C. for 0.5 to 48 hours can be mentioned. In addition, as a method of treating the above product with mixed acid, for example, a method of mixing the above product in a mixed solution of concentrated sulfuric acid and concentrated nitric acid (concentrated sulfuric acid: concentrated nitric acid = 3: 1) to 0.01 to 10 mass % and reacting at a temperature of 0 to 100 ° C. for 0.5 to 48 hours can be mentioned. The mixing ratio of the mixed acid (concentrated sulfuric acid: concentrated nitric acid) can be adjusted within the range of 1: 10 to 10: 1 according to the amount of single-walled carbon nanotubes in the above product. An example of a method for treating the above product with nitric acid is to mix the above product with nitric acid having a concentration of 40 to 80% by mass so that the concentration is 0.01 to 10% by mass, and react the mixture at a temperature of 60 to 150° C. for 0.5 to 48 hours.
[0060] By subjecting the above-mentioned product to an oxidation treatment, impurities such as amorphous carbon and single-walled carbon nanotubes having low heat resistance in the product can be selectively removed, and the purity of several graphene layers, particularly carbon nanotubes having 2 to 5 layers, can be improved. At the same time, by subjecting the product to an oxidation treatment, functional groups are added to the surface of the carbon nanotubes, improving the affinity with the dispersion medium and additives and improving the dispersibility. Among the above-mentioned oxidation treatments, a treatment using nitric acid is preferred.
[0061] The oxidation treatment may be performed immediately after obtaining carbon nanotubes before the oxidation treatment, or after another purification treatment. For example, when iron / magnesia is used as a catalyst, the oxidation treatment may be performed after a purification treatment with an acid such as hydrochloric acid to remove the catalyst before the oxidation treatment, or the oxidation treatment may be performed after the purification treatment to remove the catalyst.
[0062] The positive electrode composition according to this embodiment contains an active material. The active material is a material capable of reversibly absorbing and releasing cations, and has a volume resistivity of, for example, 1×10 4The lithium-containing composite oxide may be a lithium-containing polyanion compound or a lithium-containing composite oxide containing manganese with a resistivity of Ω·cm or more. Examples of the lithium-containing composite oxide containing manganese include LiMnO2, LiMnO3, LiMn2O3, Li 1+x Mn 2-x Lithium manganese oxide such as LiMnO4 (where x = 0 to 0.33); x Ni y Co z O2 (however, x+y+z=1, 0≦y<1, 0≦z<1, 0≦x<1), Li 1+x Mn 2-x-y M y O4 (x=0~0.33, y=0~1.0, 2-xy>0), LiMn 2-x M x Examples of the lithium-containing polyanion compound include polyanion compounds such as LiFePO4, LiMnPO4, and Li2MPO4F (wherein M is at least one metal selected from Co, Ni, Fe, Cr, and Zn). In each composition formula, M is at least one metal selected from the group consisting of Fe, Co, Ni, Al, Cu, Mg, Cr, Zn, and Ta.
[0063] Average particle diameter of active material (D 50 ) may be 20 μm or less or 10 μm or less from the viewpoint that the binding property between the conductive material and the binder is sufficiently excellent and a battery having excellent cycle characteristics can be easily obtained. 50 ) can be measured by laser light scattering.
[0064] The content of the active material may be, for example, 84% by mass or more based on the total mass of the solid contents in the positive electrode composition, and from the viewpoint of increasing the energy density of the battery, may be 85% by mass or more, 86% by mass or more, or 87% by mass or more. The content of the active material may be, for example, 92% by mass or less based on the total mass of the solid contents in the positive electrode composition, and from the viewpoint of increasing the output of the battery, may be 91% by mass or less, 90% by mass or less, or 89% by mass or less. That is, the content of the active material may be, for example, 84 to 92 mass%, 84 to 91 mass%, 84 to 90 mass%, 84 to 89 mass%, 85 to 92 mass%, 85 to 91 mass%, 85 to 90 mass%, 85 to 89 mass%, 86 to 92 mass%, 86 to 91 mass%, 86 to 90 mass%, 86 to 89 mass%, 87 to 92 mass%, 87 to 91 mass%, 87 to 90 mass%, or 87 to 89 mass%, based on the total mass of the solid contents in the positive electrode composition.
[0065] The positive electrode composition according to the present embodiment contains a binder. Examples of the binder include polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene copolymer, and (meth)acrylic acid ester copolymer. The polymer structure of the binder may be, for example, a random copolymer, an alternating copolymer, a graft copolymer, or a block copolymer. The binder may be polyvinylidene fluoride from the viewpoint of excellent voltage resistance.
[0066] The content of the binder may be, for example, 1.0% by mass or more based on the total mass of the solid content in the positive electrode composition, and from the viewpoint of further increasing the binding property of the positive electrode plate and improving the cycle characteristics, it may be 1.5% by mass or more, 2.0% by mass or more, or 3.0% by mass or more. The content of the binder may be, for example, 5.0% by mass or less based on the total mass of the solid content in the positive electrode composition, and from the viewpoint of further reducing the resistance of the positive electrode plate and improving the discharge rate characteristics, it may be 4.5% by mass or less, 4.0% by mass or less, or 3.5% by mass or less. That is, the content of the binder may be, for example, 1.0 to 5.0 mass%, 1.0 to 4.5 mass%, 1.0 to 4.0 mass%, 1.0 to 3.5 mass%, 1.5 to 5.0 mass%, 1.5 to 4.5 mass%, 1.5 to 4.0 mass%, 1.5 to 3.5 mass%, 2.0 to 5.0 mass%, 2.0 to 4.5 mass%, 2.0 to 4.0 mass%, 2.0 to 3.5 mass%, 3.0 to 5.0 mass%, 3.0 to 4.5 mass%, 3.0 to 4.0 mass%, or 3.0 to 3.5 mass%, based on the total mass of the solids in the positive electrode composition.
[0067] The positive electrode composition according to the present embodiment may further contain other additives in addition to the active material, conductive material, and binder. For example, the other additives may be polyvinylpyrrolidone, polyvinyl imidazole, polyethylene glycol, polyvinyl alcohol, polyvinyl butyral, carboxymethyl cellulose, acetyl cellulose, carboxylic acid-modified (meth)acrylic acid ester copolymer, etc., from the viewpoint of improving dispersibility.
[0068] The positive electrode composition according to the present embodiment can be manufactured by a known method. For example, the positive electrode composition can be obtained by mixing carbon black, carbon nanotubes, an active material, a binder, and a dispersion medium (and other additives) using a ball mill, a sand mill, a two-axis kneader, a rotation-revolution type mixer, a planetary mixer, a dispersing mixer, etc. Carbon black and carbon nanotubes may be separately charged into a mixer, or may be mixed in advance.
[0069] The method for producing the positive electrode in this embodiment is not particularly limited, and may be performed using a conventionally known method for producing a positive electrode, but may be produced, for example, by the following method. That is, after the dispersion liquid is applied onto a metal foil collector such as aluminum, the dispersion medium contained in the mixture of the positive electrode composition and the dispersion medium of this embodiment is removed by heating, and the positive electrode composition is formed into a film on the surface of the collector. Furthermore, the collector and the electrode mixture layer are pressed together by a roll press or the like to obtain the desired positive electrode.
[0070] The method for producing the negative electrode in this embodiment is not particularly limited, and may be performed using a conventionally known method for producing a negative electrode, but may be produced, for example, by the following method. That is, a negative electrode composition containing artificial graphite or the like is applied onto a metal foil current collector such as copper, and then the dispersion medium is removed, and the negative electrode composition is formed into a film on the surface of the current collector. The current collector and the electrode mixture layer are then pressed together by a roll press or the like to obtain the desired negative electrode.
[0071] The method for producing the battery in this embodiment is not particularly limited and may be performed using a conventional method for producing secondary batteries, but the battery may also be produced, for example, by the following method: That is, the battery can be produced by disposing a polyolefin microporous membrane as an insulating layer between the positive electrode and the negative electrode, and injecting a nonaqueous electrolyte into the voids of the positive electrode, the negative electrode, and the polyolefin microporous membrane until the nonaqueous electrolyte is sufficiently saturated.
[0072] The applications of the battery in this embodiment are not particularly limited, and the battery can be used in a wide range of fields, for example, portable AV devices such as digital cameras, video cameras, portable audio players, and portable LCD televisions, portable information terminals such as notebook personal computers, smartphones, and mobile PCs, as well as portable game devices, power tools, electric bicycles, hybrid automobiles, electric automobiles, and power storage systems. EXAMPLES
[0073] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0074] <Example 1> (Carbon Black) The raw material, acetylene, was pumped at 12 Nm from a nozzle installed upstream of the carbon black reactor (furnace length 6 m, furnace diameter 0.65 m). 3 / h, toluene 32kg / h, oxygen 22Nm 3 / h to produce carbon black, which was then collected in a bag filter installed downstream of the reactor. The carbon black was then passed through a dry cyclone device and an iron removal magnet before being collected in a tank. The acetylene, toluene, and oxygen were heated to 115°C before being supplied to the reactor to produce carbon black A. The carbon black A thus obtained had a BET specific surface area of 240 m 2 / g, the average primary particle size was 20 nm, and the crystallite size (Lc) was 16 Å.
[0075] Carbon black A was set in an evolved gas mass spectrometer (GC / MS: Shimadzu Corporation, QP-2010, pyrolyzer: Frontier Labs, Py-2020iD), and after holding at 50°C for 5 minutes in atmospheric pressure He flow, the temperature was raised to 800°C at 80°C / min, and mass analysis of the components desorbed by heating was performed under the following conditions, and the peak area S1 of the peak with mass number m / z 57 and the peak area S2 of the peak with mass number m / z 128 of the obtained carbon black A were measured. The ratio (S2 / S1) was calculated from the peak area S1 of the peak with mass number m / z 57 and the peak area S2 of the peak with mass number m / z 128 of the measured carbon black A, and was 0.40. Column: Ultra ALLOY-DTM (length 2.5 m, 0.15 mm I.D., 0.47 mm O.D.) manufactured by Frontier Labs Sample introduction temperature: 300℃ Column temperature: 300℃, held for 80 minutes Split ratio: 30:1 Column flow rate: 1.0 mL / min Ionization method: EI Measurement mass range: m / z=10-200
[0076] (Carbon black slurry) Carbon black A, N-methyl-2-pyrrolidone (referred to as NMP) as a dispersion medium, and polyvinyl alcohol (Poval B05, manufactured by Denka Co., Ltd.) as a dispersant were prepared. 1.0% by mass of polyvinyl alcohol and 10.0% by mass of carbon black A were added to 89.0% by mass of NMP, and the mixture was stirred for 120 minutes with a planetary mixer (Hivis Dispermix 3D-5, manufactured by Primix Co., Ltd.) to prepare a slurry containing carbon black A. The obtained slurry was put into a bead mill (Mugen Flow MGF2-ZA, manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia beads (diameter 0.5 mm) and subjected to a dispersion treatment. After the dispersion treatment, the zirconia beads were removed by filtration to prepare a slurry of carbon black A.
[0077] (Positive electrode composition) Carbon black A slurry was prepared using carbon black A, and carbon black A slurry was prepared using carbon black A with an average diameter of 6 nm and a BET specific surface area of 300 m 2 An NMP dispersion of carbon nanotubes (manufactured by CNano, "Flotube6000") having an average particle diameter D 50 A lithium nickel manganese cobalt oxide having a diameter of 10 μm (Beijing Dangsheng Co., Ltd., "ME6E"), an NMP solution of polyvinylidene fluoride as a binder (Kureha Corporation, "L#7208"), and NMP as a dispersion medium were prepared. The active material was adjusted to 97.0 mass%, carbon black to 0.7 mass%, carbon nanotubes to 0.3 mass%, and the binder to 2.0 mass% in terms of solid ratio, and NMP was added until the viscosity became coatable, and the mixture was mixed until it became uniform using a planetary centrifugal mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a positive electrode composition.
[0078] (positive electrode) The prepared positive electrode composition (NMP dispersion) was applied to one side of an aluminum foil (manufactured by UACJ) having a thickness of 15 μm by an applicator to prepare a laminate, which was then placed in a dryer and pre-dried at 105 ° C for 1 hour to completely remove the NMP. The dried laminate was then pressed with a roll press at a linear pressure of 200 kg / cm to adjust the thickness of the entire laminate to 80 μm. The laminate was then vacuum-dried at 170 ° C for 3 hours to completely remove residual moisture, and a positive electrode having a current collector and a composite layer was obtained.
[0079] (Negative electrode) Pure water (Kanto Chemical Co., Ltd.) was prepared as a solvent, artificial graphite (Hitachi Chemical Co., Ltd., "MAG-D") as a negative electrode active material, styrene butadiene rubber (Zeon Corporation, "BM-400B", hereinafter referred to as SBR) as a binder, and carboxymethyl cellulose (Daicel Corporation, "D2200", hereinafter referred to as CMC) as a dispersant. Next, CMC was weighed and mixed so that the solid content was 1 mass% and artificial graphite was 97 mass% in solid content, and pure water was added to this mixture, and the mixture was mixed until it was uniform using a rotation-revolution type mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a mixture. Next, SBR was weighed so that the solid content was 2 mass%, and added to the obtained mixture, and the mixture was mixed until it was uniform using a rotation-revolution type mixer (Thinky Corporation, Awatori Rentaro ARV-310) to obtain a negative electrode composition. Next, the negative electrode composition was applied to a copper foil (manufactured by UACJ) having a thickness of 10 μm by an applicator to prepare a laminate, which was then placed in a dryer and pre-dried at 60° C. for 1 hour. Next, the laminate was pressed with a linear pressure of 50 kg / cm using a roll press machine to adjust the thickness of the entire laminate to 60 μm. Next, the laminate was vacuum-dried at 120° C. for 3 hours to completely remove residual moisture, and a negative electrode having a current collector and a composite layer was obtained.
[0080] (battery) In a dry room controlled to a dew point of -50°C or less, the prepared positive electrode was processed to 40 x 40 mm, and the prepared negative electrode was processed to 44 x 44 mm, and then an aluminum tab was welded to the positive electrode and a nickel tab was welded to the negative electrode. The composite coated surfaces of the positive electrode and negative electrode were arranged to face each other in the center, and a polyolefin microporous membrane processed to 45 x 45 mm was placed between the positive electrode and negative electrode. Next, a sheet-like exterior cut and processed to a 70 x 140 mm square was folded in half at the center of the long side. Next, the exterior was arranged so that the aluminum tab for the positive electrode and the nickel tab for the negative electrode were exposed to the outside of the exterior, and the laminate of the positive electrode / polyolefin microporous membrane / negative electrode was sandwiched between the folded exterior. Next, using a heat sealer, two sides of the exterior, including the side where the aluminum tab for the positive electrode and the nickel tab for the negative electrode were exposed, were heat-sealed, and then 2 g of electrolyte (manufactured by Kishida Chemical, a solution containing ethylene carbonate / diethyl carbonate = 1 / 2 (volume ratio) and 1 M LiPF6 solution) was poured into the other side that was not heat-sealed, allowing the electrolyte to fully soak into the positive electrode, negative electrode, and polyolefin microporous membrane. After that, the remaining side of the exterior was heat-sealed while reducing the internal pressure using a vacuum heat sealer, to obtain a lithium-ion secondary battery.
[0081] <Example 2> The raw material, acetylene, was pumped at 12 Nm from a nozzle installed upstream of the carbon black reactor (furnace length 6 m, furnace diameter 0.65 m). 3 / h, toluene 32kg / h, oxygen 21Nm 3 / h to produce carbon black, which was then collected in a bag filter installed downstream of the reactor. The carbon black was then passed through a dry cyclone device and an iron removal magnet before being collected in a tank. The acetylene, toluene, and oxygen were heated to 115°C before being supplied to the reactor to produce carbon black B. The carbon black B thus obtained had a BET specific surface area of 178 m 2 / g, the average primary particle diameter was 22 nm, and the crystallite size (Lc) was 17 Å. The ratio (S2 / S1) of Carbon Black B was calculated in the same manner as for Carbon Black A, and was found to be 0.44.
[0082] A battery was produced in the same manner as in Example 1, except that carbon black B was used instead of carbon black A in Example 1.
[0083] <Example 3> The NMP dispersion of the carbon nanotubes of Example 1 having an average diameter of 9 nm and a BET specific surface area of 250 m 2 A battery was produced in the same manner as in Example 1, except that the electrolyte was changed to an NMP dispersion of carbon nanotubes having a mean diameter / BET specific surface area of 0.036 (manufactured by CNano, "Flotube7000").
[0084] <Example 4> Carbon black A in Example 1 has a BET specific surface area of 133 m 2 A battery was fabricated in the same manner as in Example 1, except that the carbon black was changed to carbon black having a molecular weight of 1.001g / g, an average primary particle diameter of 26 nm, and a crystallite size (Lc) of 25 Å (manufactured by Denka, "Li-435"). The ratio (S2 / S1) of carbon black Li-435 was calculated in the same manner as carbon black A and was found to be 0.23.
[0085] <Example 5> The raw material, acetylene, was pumped at 12 Nm from a nozzle installed upstream of the carbon black reactor (furnace length 6 m, furnace diameter 0.65 m). 3 / h, toluene 32kg / h, oxygen 20Nm 3 / h to produce carbon black, which was then collected in a bag filter installed downstream of the reactor. The carbon black was then passed through a dry cyclone device and an iron removal magnet before being collected in a tank. The acetylene, toluene, and oxygen were heated to 115°C before being supplied to the reactor to produce carbon black C. The carbon black C obtained had a BET specific surface area of 165 m 2 / g, the average primary particle diameter was 23 nm, and the crystallite size (Lc) was 18 Å. The ratio (S2 / S1) of Carbon Black C was calculated in the same manner as for Carbon Black A, and was found to be 0.42.
[0086] A battery was produced in the same manner as in Example 1, except that carbon black C was used instead of carbon black A in Example 1.
[0087] <Example 6> The NMP dispersion of the carbon nanotubes of Example 1 having an average diameter of 12 nm and a BET specific surface area of 180 m 2 A battery was produced in the same manner as in Example 1, except that the electrolyte was changed to an NMP dispersion of carbon nanotubes having a molecular weight of 0.01 / g and an average diameter / BET specific surface area of 0.067 (manufactured by CNano, "Flotube9000").
[0088] <Example 7> A battery was fabricated in the same manner as in Example 1, except that the amounts of carbon black and carbon nanotubes added were changed so that the carbon black content was 0.5 mass% and the carbon nanotube content was 0.5 mass%, based on the total mass of the solids in the positive electrode composition.
[0089] <Example 8> A battery was fabricated in the same manner as in Example 1, except that the amounts of carbon black and carbon nanotubes added were changed so that the carbon black content was 0.9 mass% and the carbon nanotube content was 0.1 mass%, based on the total mass of the solids in the positive electrode composition.
[0090] <Example 9> The raw material, acetylene, was pumped at 12 Nm from a nozzle installed upstream of the carbon black reactor (furnace length 6 m, furnace diameter 0.65 m). 3 / h, toluene 32kg / h, oxygen 26Nm 3 / h to produce carbon black, which was then collected in a bag filter installed downstream of the reactor. The carbon black was then passed through a dry cyclone device and an iron removal magnet before being collected in a tank. The acetylene, toluene, and oxygen were heated to 115°C before being supplied to the reactor to produce carbon black D. The carbon black D thus obtained had a BET specific surface area of 370 m 2 / g, the average primary particle diameter was 18 nm, and the crystallite size (Lc) was 20 Å. The ratio (S2 / S1) of Carbon Black D was calculated in the same manner as for Carbon Black A, and was found to be 0.25.
[0091] A battery was produced in the same manner as in Example 1, except that the carbon black in Example 1 was changed to Carbon Black D.
[0092] <Example 10> The active material of Example 1 was treated to have an average particle diameter D 50 A battery was fabricated in the same manner as in Example 1, except that the amount of carbon black and carbon nanotubes added was changed to 0.9 mass% and the amount of carbon nanotubes added was changed to 0.1 mass%, based on the total mass of the solid content in the positive electrode composition.
[0093] <Example 11> Carbon black A in Example 1 was changed to carbon black B. The NMP dispersion of carbon nanotubes in Example 1 was 2 A battery was produced in the same manner as in Example 1, except that the positive electrode composition was changed to an NMP dispersion of carbon nanotubes (manufactured by CNano, "Flotube7000") having a mean diameter / g and an average diameter / BET specific surface area of 0.036, and the amounts of carbon black and carbon nanotubes added were changed so that the carbon black content was 0.1 mass % and the carbon nanotube content was 0.9 mass %, based on the total mass of the solid content in the positive electrode composition.
[0094] <Comparative Example 1> The carbon black of Example 1 has a BET specific surface area of 62 m 2A battery was produced in the same manner as in Example 1, except that the carbon black was changed to carbon black having a molecular weight of 1.01 kg / g, an average primary particle diameter of 36 nm, and a crystallite size (Lc) of 20 Å (manufactured by Imerys Graphite & Carbon Co., Ltd., "SuperPLi"). The ratio (S2 / S1) of carbon black SuperPLi was calculated in the same manner as for carbon black A, and was found to be 1.12.
[0095] <Comparative Example 2> The carbon black of Example 1 has a BET specific surface area of 87 m 2 A battery was produced in the same manner as in Example 1, except that the carbon black was changed to carbon black (LiTX-HP) having a molecular weight of 1.01 kg / g, an average primary particle diameter of 25 nm, and a crystallite size (Lc) of 23 Å. In addition, the ratio (S2 / S1) of carbon black LiTX-HP was calculated in the same manner as carbon black A and was found to be 1.28.
[0096] <Comparative Example 3> A battery was produced in the same manner as in Example 1, except that carbon black A in Example 1 was changed to carbon black C and carbon nanotubes were not used.
[0097] <Comparative Example 4> The NMP dispersion of the carbon nanotubes of Example 1 having an average diameter of 9 nm and a BET specific surface area of 250 m 2 A battery was produced in the same manner as in Example 1, except that the electrolyte was changed to an NMP dispersion of carbon nanotubes (manufactured by CNano, "Flotube7000") having a molecular weight of 0.01 / g and an average diameter / BET specific surface area of 0.036, and no carbon black was used.
[0098] <Comparative Example 5> The carbon black of Example 1 was mixed with a BET specific surface area of 820 m 2 A battery was fabricated in the same manner as in Example 1, except that the carbon black was changed to carbon black having a molecular weight of 1.01g, an average primary particle diameter of 40 nm, and a crystallite size (Lc) of 16 Å (manufactured by Lion Corporation, "ECP"). The ratio (S2 / S1) of carbon black ECP was calculated in the same manner as carbon black A, and was found to be 2.06.
[0099] <Comparative Example 6> The NMP dispersion of carbon nanotubes of Example 1 having an average diameter of 12 nm and a BET specific surface area of 175 m 2 A battery was produced in the same manner as in Example 1, except that the electrolyte was changed to an NMP dispersion of carbon nanotubes (manufactured by Nanocyl Corporation, “NC7000”) having a mean diameter / g and an average diameter / BET specific surface area of 0.069.
[0100] <Comparative Example 7> The NMP dispersion of carbon nanotubes of Example 1 having an average diameter of 32 nm and a BET specific surface area of 110 m 2 A battery was produced in the same manner as in Example 1, except that the electrolyte was changed to an NMP dispersion of carbon nanotubes (manufactured by Tokyo Chemical Industry Co., Ltd., "MWNT") having a specific surface area of 0.29 / g and an average diameter / BET specific surface area of 0.29.
[0101] <Comparative Example 8> The carbon black of Example 1 was mixed with a BET specific surface area of 120 m 2 A battery was fabricated in the same manner as in Example 1, except that the carbon black used was changed to carbon black having a molecular weight of 1.01 kg / g, an average primary particle diameter of 26 nm, and a crystallite size (Lc) of 27 Å (manufactured by Orion, "YS"). The ratio (S2 / S1) of carbon black YS was calculated in the same manner as carbon black A and was found to be 0.92.
[0102] <Comparative Example 9> The carbon black of Example 1 has a BET specific surface area of 343 m 2 A battery was produced in the same manner as in Example 1, except that the carbon black used was changed to carbon black having a molecular weight of 1.0 / g, an average primary particle diameter of 16 nm, and a crystallite size (Lc) of 14 Å (manufactured by Cabot Corporation, "BLACK PEARLS 1000"). In addition, the ratio (S2 / S1) of carbon black BLACK PEARLS 1000 was calculated in the same manner as for carbon black A, and was found to be 3.42.
[0103] <Comparative Example 10> The NMP dispersion of carbon nanotubes of Example 1 having an average diameter of 2.5 nm and a BET specific surface area of 740 m2 A battery was produced in the same manner as in Example 1, except that the positive electrode composition was changed to an NMP dispersion of carbon nanotubes (Sigma-Aldrich Corporation, "Signis FW100") having a mean diameter / g and an average diameter / BET specific surface area of 0.003, and the amounts of carbon black and carbon nanotubes added were changed so that the carbon black content was 0.9 mass% and the carbon nanotube content was 0.1 mass%, based on the total mass of the solid content in the positive electrode composition.
[0104] The battery performance of the produced lithium ion secondary batteries was evaluated by the following method.
[0105] (Battery evaluation) [Internal resistance] The prepared battery was charged at 25°C at 4.3V with a constant current and constant voltage of 0.2C, and then discharged to 3.0V at a constant current of 0.2C. Next, after 5 cycles of charge / discharge under the same conditions, it was charged to a charge depth of 50%. Then, impedance measurements were performed at a frequency range of 10MHz to 0.001Hz and an oscillation voltage of 5mV to measure the internal resistance. The measurement results of the internal resistance are shown in Tables 1 to 4.
[0106] [Discharge rate characteristics (rate capacity retention)] The battery thus prepared was charged at 25°C at a constant current of 4.3V and a constant voltage of 0.2C, and then discharged to 3.0V at a constant current of 0.2C. Next, the battery was again recovered and charged at a constant current and voltage of 4.3V and a constant voltage of 0.2C, and then discharged to 3.0V at a constant current of 0.2C, and the discharge capacity at this time was measured. Next, the recovery charge condition was set to 4.3V, a constant current and voltage of 0.2C, and charging was performed, while the discharge current was changed stepwise to 0.5C, 1C, 2C, and 3C, and recovery charge and discharge were repeated to measure the discharge capacity for each discharge current. As an index of the discharge rate characteristics of the battery, the capacity retention rate at 3C discharge relative to 0.2C discharge was calculated as the rate capacity retention rate. The calculation results of the rate capacity retention rate are shown in Tables 1 to 4.
[0107] [Cycle characteristics (cycle capacity retention rate)] The prepared battery was charged at 25°C at a constant current and constant voltage of 4.3 V and limited to 1 C, and then discharged to 3.0 V at a constant current of 1 C. The above charge and discharge were repeated 500 cycles, and the discharge capacity at each cycle was measured. As an index of the cycle characteristics of the battery, the capacity retention rate after 500 cycles relative to the capacity retention rate after 1 cycle was calculated as the cycle capacity retention rate. The calculation results of the cycle capacity retention rate are shown in Tables 1 to 4.
[0108] [Table 1]
[0109] [Table 2]
[0110] [Table 3]
[0111] [Table 4]
[0112] From the results in Tables 1 to 4, it was confirmed that the batteries produced using the positive electrode compositions according to the above-described embodiments had low internal resistance and excellent discharge rate characteristics and cycle characteristics.
Claims
1. Contains carbon black, carbon nanotubes, an active material, and a binder; The carbon black has a viscosity of 100 to 400 m 2 / g BET specific surface area and a crystallite size (Lc) of 15 to 26 Å; the carbon nanotubes have an average diameter of 5 to 15 nm; The ratio of the average diameter to the BET specific surface area of the carbon nanotubes (average diameter / BET specific surface area) is 0.01 to 0.068 nm / (m 2 / g), A positive electrode composition, wherein a ratio (S 2 / S 1 ) of a peak area (S 2 ) of a peak with mass number m / z 128 to a peak area (S 1 ) of a peak with mass number m / z 57 detected by thermal desorption spectrometry of the carbon black is 0.2 to 1.
9.
2. 2. The positive electrode composition according to claim 1, wherein the carbon black has an average primary particle size of 17 to 30 nm.
3. 2. The positive electrode composition of claim 1, wherein the crystallite size (Lc) of the carbon black is 15 to 20 Å.
4. The BET specific surface area of the carbon black is 170 to 400 m 2 / g.
5. 2. The cathode composition of claim 1, wherein the average diameter of the carbon nanotubes is between 5 and 10 nm.
6. 2. The positive electrode composition according to claim 1, wherein the content of the carbon black is 40 to 90 mass % based on the total content of the carbon black and the carbon nanotubes.
7. A positive electrode comprising the positive electrode composition according to any one of claims 1 to 6.
8. A battery comprising the positive electrode of claim 7.
Citation Information
Patent Citations
Nonaqueous electrolytic material
JP2001126733A
Conductive slurry, electrode slurry and electrode for electric double-layer capacitor using the slurry
JP2008227481A
Electrode for lithium ion battery and its manufacturing method
JP2010238575A
Positive electrode for lithium secondary battery and lithium secondary battery using the same
JP2012038724A
Electrode composition for battery
JP2016025077A
